Identification of Slow Learner with Proposed Innovative NDLI Resources Utilization Approach - Madhuri N. Gedam,; Dr. Deven Shah, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The National Digital Library of India (NDLI) is National Mission on Education set by Ministry of Education of Govt. of India. It is developed, operated, and maintained by Indian Institute of Technology Kharagpur. It is intended to provide education for all through integrated knowledge base ranging from school level to researcher’s level considering different languages and easily available at the fingertips. The SWOT analysis of contents of NDLI portal is done in this paper. Authors proposed new pedagogy to map the contents of various engineering branches available on NDLI portal with university curriculum to achieve the course outcomes (CO). The analysis of student’s results through quizzes and tests is used for identification of slow, medium, and fast learners of different courses.
Keywords: Digital Library; NDLI; CO; SWOT; Slow Learners